2014
DOI: 10.1039/c4ra06997h
|View full text |Cite
|
Sign up to set email alerts
|

Degradable, silyl ether thiol–ene networks

Abstract: The polymerization of silyl ether containing thiols and alkenes results in tunable, degradable thermosets with potential in implantable electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The T g s from XL 1 and XL 2 are comparable to the T g s of most epoxy networks of bisphenol A diglycidyl ether cured with conventional aliphatic amines, while the T g s for XL 3 and XL 4 are lower. The observed T g s from both DSC and DMA measurements were higher than those reported for polyurethane biodegradable networks obtained from epoxy amine reactions, and suggest that these networks could be utilized in applications requiring degradable polymers with higher T g s …”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The T g s from XL 1 and XL 2 are comparable to the T g s of most epoxy networks of bisphenol A diglycidyl ether cured with conventional aliphatic amines, while the T g s for XL 3 and XL 4 are lower. The observed T g s from both DSC and DMA measurements were higher than those reported for polyurethane biodegradable networks obtained from epoxy amine reactions, and suggest that these networks could be utilized in applications requiring degradable polymers with higher T g s …”
Section: Resultsmentioning
confidence: 66%
“…The presence of hydrolyzable SiO bonds in the curing agents affords degradable characteristics . The curing agents were selected so that the degradation rate could be controlled by the number of SiO bonds and the extent of crosslink density estimated from the NH‐functionality .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(silyl ether)s containing SiOC bonds in their main chains are thermostable and have long been a commercial interest as degradable plastic, matrix for controlled release of drugs and membrane materials . However, partly due to sensitivity of the SiOC bond under acidic or basic conditions,[11c,14] poly(silyl ether)s are usually synthesized through the cross‐dehydro coupling of α,ω‐diols with dihydrosilanes or the hydrosilylation of α,ω‐dicarbonyl compounds (aldehydes and ketones) with dihydrosilane by the traditional ruthenium[16a,17] and rhodium[16b,c] based catalytic systems. The mechanism proposed by Ojima et al in 1975 is shown as Scheme , which reveals that the catalysts based on ruthenium and rhodium transition metals experience the redox process to afford the driving force for the SiH bond cleavage and its insertion into CO double bond, an “insertion‐propagation” process.…”
Section: Introductionmentioning
confidence: 99%